Real-Business-Cycle Models and the Forecastable Movements in Output, Hours, and Consumption - Rotemberg, Julio J.; Woodford, Michael (American Economic Review, 1996)
We study the movements in output, consumption and hours that are forecastable from a VAR and analyze how they differ from those predicted by standard real-business-cycle models. We show that actual forecastable movements in output have a variance about one hundred times larger than those predicted by the model. We also find that forecastable changes in the three series are strongly positively correlated with each other. On the other hand, for parameters whose implications are plausible in other respects, the model implies that output, consumption, and hours should not all be expected to move in the same direction